Thrombin-induced apoptosis in neurons through activation of c-Jun-N-terminal kinase. (2nd January 2017) - Bao, Lei; Zu, Jie; He, Qianqian; Zhao, Hui; Zhou, Su; Ye, Xinchun; Yang, Xinxin; Zan, Kun; Zhang, Zuohui; Shi, Hongjuan; Cui, Guiyun
Abstract: Context: Studies have shown that thrombin activation played a central role in cell injuries associated with intracerebral hemorrhage (ICH). Objective : Here, our study investigated the cytotoxicity of thrombin on neurons, and determined the involvement of JNK pathways in thrombin-induced neuronal apoptosis. Materials and methods: Primary cultured neurons were treated with different doses of thrombin. Some neurons were given either SP600125 or vehicle. LDH release assay and flow cytometry were used to measure neuronal apoptosis caused by thrombin. The activation of JNK and capases-3 were measured by Western blot. Results: Our results showed large doses of thrombin that increased the LDH release, the level of cleaved caspase-3 and apoptosis rate of neurons. JNK was activated by thrombin in a time-dependent manner. Administration of SP600125 protects neurons from thrombin-induced apoptosis. Conclusion: These data indicate that the activation of JNK is crucial for thrombin-induced neuronal apoptosis, and inhibition of JNK may be a potential therapeutic target for ICH.